The sublime object of psychiatry : schizophrenia in clinical and cultural theory - Woods, Angela (International perspectives in philosophy and psychiatry., 2011)
"Schizophrenia has been one of psychiatry's most contested diagnostic categories. It has also served as a metaphor for cultural theorists to interpret modern and postmodern understandings of the self. These radical, compelling, and puzzling appropriations of clinical accounts of schizophrenia have been dismissed by many as illegitimate, insensitive and inappropriate. Until now, no attempt has been made to analyse them systematically, nor has their significance for our broader understanding of this most 'ununderstandable' of experiences been addressed. The Sublime Object of Psychiatry is the first book to study representations of schizophrenia across a wide range of disciplines and discourses: biological and phenomenological psychiatry, psychoanalysis, critical psychology, antipsychiatry, and postmodern philosophy. In part one, Woods offers a fresh analysis of the foundational clinical accounts of schizophrenia, concentrating on the work of Emil Kraepelin, Eugen Bleuler, Karl Jaspers, Sigmund Freud and Jacques Lacan. In the second part of the book, she examines how these accounts were critiqued, adapted, and mobilised in the 'cultural theory' of R D Laing, Thomas Szasz, Gilles Deleuze, Felix Guattari, Louis Sass, Fredric Jameson and Jean Baudrillard. Using the aesthetic concept of the sublime as an organising framework, Woods explains how a clinical diagnostic category came to be transformed into a potent metaphor in cultural theory, and how, in that transformation, schizophrenia came to be associated with the everyday experience of modern and postmodern life. Susan Sontag once wrote: 'Any important disease whose causality is murky, and for which treatment is ineffectual, tends to be awash in significance'. The Sublime Object of Psychiatry does not provide an answer to the question 'What is schizophrenia?', but instead brings clinical and cultural theory into dialogue in order to explain how schizophrenia became 'awash in significance'"--